Impact of Hypermedia-based Adverb Learning on Speaking Skill Development: An Experimental Study - Mohideen Bawa Nowzath; Singanayagam Umashankar; M.R Rishad Muhammed (Demagogi: Journal of Social Sciences, Economics and Education, 2025)
Hypermedia-based adverb learning refers to facilitate adverbs including graphs, images, animation, sound and hypertext with constructive knowledge. It exhibits a central part in the success of the students learning English as a second language. The study was to identify the productivity of hypermedia-based adverb learning on the performance in the speaking skill development of the students in the Higher National Diploma in English. It was conducted in Higher National Diploma in English course of Advanced Technological Institute - Sammanthurai at Sri Lanka Institute of Advanced Technological Education under the Ministry of Education. 90 students from Higher National Diploma in English – class - A were used as the experimental group and the equivalent numbers of students from Higher National Diploma in English – class - B were taken as the controlled group. A pre-test with picture description was led for both the groups to find out the previous proficiency level of speaking skill with adverbs of the students to compare them and the mean differences were found to be negligible for both the groups from the pre-test. Later, the experimental group used hypermedia-based adverb learning based on selected learning strategies: activities and arrangements in presentation with video and audio-based system for six months with ninety hours learning while the controlled group was taught without the use of hypermedia-based adverb learning. After six months a post-test with picture description was conducted for both the groups. When the post-test was conducted the mean (-0.091) was slightly improved for the group - B than the pre-test, and the mean (-2.871) was significantly improved for the group - A in the post-test. Thus, it is found that there is a positive relationship between the hyper-media based adverb learning and the performance in speaking skill development with adverbs. The research findings indicate that hyper-media based adverb learning improves speaking skill development with adverbs of the learners of English as a second language.